How can emotional intelligence organizations improve job performance of job candidates? - Nadhita, Galuh; Mugiarso, Heru; Mulawarman (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Prospective workers need to have good work performance to be able to increase competitiveness and work productivity. Candidates who have the ability to monitor their emotions will find it easier to achieve good performance. Therefore, the purpose of this study was to determine the effect of emotional intelligence organizations to work performance of prospective workers. Methods: Quantitative method was used in this study with ex post facto as the research design. The subjects of this study were 155 trainees at Semarang Job Training Center 1 class of 2023. In this study, the hypothesis was tested using a simple linear regression test. Finding: This study found the level of organizational emotional intelligence of trainees is in the low category, the level of job performance is in the low category, and emotional intelligence organizations has a positive influence on the job performance of trainees. This research found that trainees with high emotional intelligence at work have good performance, and vice versa. Conclusion: Further researchers can use other methods to obtain more comprehensive results and add or change other variables relevant to job performance. This reaserch suggest that career guidance services play a crucial role in enhancing job performance for job candidates. Novelty/Originality of this study: This study provides a new perspective on the importance of organizational emotional intelligence in improving the job performance of prospective workers. This study offers insights that can be directly applied in developing training programs at the Job Training Center, focusing on improving emotional intelligence to increase the competitiveness and productivity of prospective workers in a competitive labour market.